Prognostic role of platelet lymphocyte ratio (PLR) among patients with hepatocellular carcinoma undergoing liver transplantation (Annals of Medical Research, 2023)
Aim: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide, but it is so aggressive that is the third most common cause of cancer related death.We aim to study the role of PLR in prognosis of HCC and to see if it can be a predictor of overall survival and disease-free survival among HCC patients that received liver transplantation in our center.Materials and Methods: This is a single center retrospective analysis of prospectively collected data. The study was carried out in liver transplant institute of Inonu University, Malatya, Turkey.  Consecutive patients that received liver transplantation for HCC and survive for at least 90 days post transplantation were included in the study. Data was collected regarding age, gender, presence or absence of cirrhosis, cause of cirrhosis, number of nodules, maximum size of the tumor, preoperative PLR, pre-transplant GGT, type of transplant, presence or absence of microvascular invasion, overall survival and disease-free survival. The study was censored on June 2022. Data was analyzed using SPSS version 25.Results: Platelet lymphocyte ratio was found to be significantly associated with some poor prognostic factors of HCC in our patients. We found that PLR is significantly associated with maximum tumor diameter (MTD) and total tumor diameter (TTD) with p=